THE URGENCY TO RE-EVALUATE FEMALE GENITAL MUTILATION PRACTICE AMONG MUSLIM COMMUNITIES IN INDONESIA - Saputro, Lucke Kharimah Pamungkas; Khairur Rijal, Najamuddin (UIN Mataram dan Asosiasi Sosiologi Agama Indonesia (ASAGI), 2022)
This article discusses the long-lasting problem of the Indonesian practice of Female Genital Mutilation/Cutting (FGM/C) among Muslim communities. With the purpose to identify the religious and medical rationalization of the FGM/C practice and if it needs to be re-evaluated. The data collection in this study was carried out through a literature study from various secondary sources. This article concludes that Indonesia's religious basis for FGM/C practice that is mandated by MUI in 2008 is full of loopholes. The rationalization and ambiguous regulations made by Permenkes No.6/2014 also create more confusion among civilians and healthcare practitioners that cause medicalization practice for FGM/C. In addition to the way of Indonesia's national and international policy that prone to the realization of international commitments and SDGs 2030. Therefore Indonesia's government needs to pay more attention to FGM/C problems as it can affect the development of Indonesia to achieve its national and international commitment.